1992
DOI: 10.2337/diab.41.10.1257
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Distinctive and Intrinsic Defects in Insulin Action in Polycystic Ovary Syndrome

Abstract: Women with PCO have a unique but poorly characterized disorder of insulin action. Obese (n = 16) and nonobese (n = 14) PCO women and age- and weight-matched normal, nondiabetic ovulatory women (obese, n = 15; nonobese, n = 17) had insulin action determined in vivo with sequential multiple insulin dose euglycemic clamps and in isolated abdominal adipocytes to clarify the mechanisms of insulin resistance. PCO resulted in significant increases in the ED50 insulin for glucose utilization in vivo (P less than 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
264
3
11

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(287 citation statements)
references
References 0 publications
9
264
3
11
Order By: Relevance
“…The association of peripheral insulin resistance and PCOS is well established. Insulin stimulates estrogen and progesterone in human granulosa cells from normal and PCOS ovaries, despite the apparent paradox of insulin resistance at classic target tissues (16). Although it has been suggested that insulin may act via the type I insulin-like growthfactor (IGF) receptor to explain the controversial findings, it has recently been shown that the action of insulin in PCOS is mediated by its own receptor (17).…”
Section: Discussionmentioning
confidence: 99%
“…The association of peripheral insulin resistance and PCOS is well established. Insulin stimulates estrogen and progesterone in human granulosa cells from normal and PCOS ovaries, despite the apparent paradox of insulin resistance at classic target tissues (16). Although it has been suggested that insulin may act via the type I insulin-like growthfactor (IGF) receptor to explain the controversial findings, it has recently been shown that the action of insulin in PCOS is mediated by its own receptor (17).…”
Section: Discussionmentioning
confidence: 99%
“…Although the glucose response was similar between groups, insulin responses were significantly greater in women with PCOS [2]. Subsequent studies using the gold standard hyperinsulinaemic-euglycaemic clamp technique have clearly indicated a reduction in insulin-mediated glucose disposal (IMGD) in women with PCOS compared with ageand BMI matched women who were reproductively normal [4,11]. Treatment of women with PCOS with metformin for 6 to 12 months is associated with improvements in IMGD measured by hyperinsulinaemic-euglycaemic clamp technique [46,47].…”
Section: Impact Of Metformin On Metabolic Features Of Pcosmentioning
confidence: 99%
“…Over the ensuing decades, it became clear that this 'reproductive' syndrome was often accompanied by metabolic features that are a consequence of insulin resistance and hyperinsulinaemia [2][3][4], for example, impairment in oral glucose tolerance, type 2 diabetes [5,6], the metabolic syndrome [7,8] and dyslipidaemia [9,10]. The magnitude of insulin resistance in PCOS is greater than that caused by excess adiposity alone; it is characterised by reduced sensitivity and responsiveness to insulin-mediated glucose utilisation, primarily in the skeletal muscle, adipose tissue and in the liver [11]. Insulin resistance and resultant hyperinsulinaemia contribute to hyperandrogenaemia in PCOS by augmenting luteinising hormone-stimulated androgen production by ovarian theca cells [12][13][14] and by inhibiting hepatic synthesis of sex hormone-binding globulin (SHBG), the latter leading to an increase in bioavailable testosterone [15].…”
Section: Introductionmentioning
confidence: 99%
“…(1990a) interviewed 102 women undergoing coronary catheterization and found that of 52 women with significant artery disease, 65% had a history of hirsutism, and therefore most likely PCOS (Conway & Jacobs, 1990) while only 32% of those with normal coronary angiography reported hirsutism. An alternative view that insulin resistance in PCOS is distinct from that in syndrome X has arisen from small studies of mostly obese women in whom a relationship between blood pressure and lipoproteins and insulin was not found (Graf et a[., 1990;Zimmerman et al, 1992, Dunaif et al, 1992.…”
Section: Coronary Artery Diseasementioning
confidence: 99%